Pengaruh Ekspor, Kurs, Inflasi, dan PDRB terhadap Nilai Tukar Petani Sub-sektor Tanaman Perkebunan Rakyat di Provinsi Jambi (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study aims to determine and analyze the development and influence of exports, exchange rates, inflation, and GRDP on the exchange rate of smallholder plantation farmers in Jambi Province. This study uses multiple linear regression analysis for the period 2009-2024 in Jambi Province. The development of exports, exchange rates, inflation, and GRDP fluctuates annually. Where the average development of exports in Jambi Province in 2009-2024 was 15.22%, the average development of exchange rates was 3.06%, the average development of inflation was 49.07%, the average development of GRDP was 6.22% and the average development of the exchange rate of smallholder plantation farmers in Jambi Province was 4.57%. The results of the study using multiple linear regression resulted in the finding that the variables of exports, exchange rates, inflation, and GRDP simultaneously influenced the exchange rate of smallholder plantation farmers in Jambi Province in 2009-2024. Meanwhile, partially, the export, exchange rate, and inflation variables have a negative effect on the exchange rate of farmers in the smallholder plantation sub-sector in Jambi Province, while the GRDP variable has a substantial positive effect on the exchange rate of farmers in the smallholder plantation sub-sector in Jambi Province in 2009-2024.